Miklošičev prispevek k skladenjski obravnavi starocerkvenoslovanskega nepredložnega mestnika - Grošelj, Robert (Slavistična revija, 2007)
The article discusses Miklošič's explanation of the syntactic usage of Slavic non-prepositional locative with respect to Old Church Slavic material. Based on the analysis of Miklošič's explanations in Der präpositionslose Local in den slavischen Sprachen (1867) and Vergleichende Grammatik der slavischen Sprachen, IV. Band Syntax (1868-1874), the author traces the developmental dynamics in Miklošič's explanation of this linguistic phenomenon, while at the same time evaluating hos works from the point of view of the modern syntactic findings about Old Church Slavic non-prepositional locative.
Keywords: locative; mestnik; Milošič, Franc; nepredložni mestnik; non-prepositional locative; Old Chruch Slavic; skladnja; sklon; stara cerkvena slovanščina; syntax